Сognitive justice: a road map for equitable inclusive learning environments - Makoelle, Tsediso (International Journal of Education and Research. Vol. 2 No. 7 July 2014, 2014)
The conceptualization of the notion of inclusive education is mostly drawn from western forms of conceptions, thought and knowledge. Few studies actually prioritize indigenous forms of knowledge in understanding the concept of inclusion based on local African livelihoods and lifestyles. This paper therefore argues that cognitive justice which articulates recognition of alternative indigenous forms of knowledge provides a theoretical basis for enabling dialogue without qualifying standards of western hegemonic discourse of thought and practice.
Keywords: cognitive justice; equitable learning; inclusive education; inclusion; indigenous knowledge